Practices Strategies To Increase Student Acceptance During The Covid-19 Pandemic Through Network Marketing ( Case Study) - Tri Yusnanto; Kanafi; Khoirul Mustofa (Cita Konsultindo Research Center, 2021)
Using network marketing, a public relations technique was used to improve university marketing during the COVID-19 epidemic. This article was written using a qualitative approach and literature study data collection techniques, such as analyzing several books containing national and international articles to obtain data in the form of text studies, which were then analyzed and concluded to obtain research results that are relevant to the research topic. The results of publishing scientific papers in the form of creating a marketing mix during the COVID-19 epidemic can be done by optimizing collage social media such as Facebook and Twitter. for example, collage websites and YouTube accounts. 2) In the context of education, marketing requires a marketing network in order for marketing to be effective and for institutions to readily obtain clients (students). 3) Public relations can study the target environment, develop marketing programs to be carried out, organize the marketing team, implement marketing programs, and track the results of marketing activities that have been carried out while deciding the marketing strategy. This is done so that higher education marketing results in customer satisfaction, allowing the target of students in higher education to be met.